Block of ATP-sensitive K+ channels in isolated mouse pancreatic beta-cells by 2,3-butanedione monoxime. - Smith, P; Williams, B; Ashcroft, F (1994)
1. The patch-clamp technique has been used to examine the action of the chemical phosphatase 2,3-butanedione monoxime (BDM) on ATP-sensitive K+ channels (KATP-channels) from mouse isolated pancreatic beta-cells in the absence of ATP and Mg2+. 2. BDM reversibly inhibited whole-cell KATP-currents with a concentration for half maximal inhibition (K(i)) of 15 +/- 1 mM and a Hill coefficient (n) of 2.5 +/- 0.2 (n = 4). 3. In outside-out patches, external BDM reversibly reduced the activity of single KATP-channels with an affinity similar to that observed in whole-cell recordings (K(i) = 11 +/- 3 mM, n = 2.0 +/- 0.3, n = 7). In inside-out patches, internally applied BDM also reversibly blocked the activity of KATP-channels (K(i) = 31 +/- 2 mM, n = 2.2 +/- 0.4, n = 8). In both excised patch configurations, BDM decreased the mean open life-time and the burst duration, thereby producing a decrease in the channel open probability. The drug had no effect on the short intraburst closed times. 4. BDM had no effect on the single-channel current amplitude. 5. The results suggest that BDM blocks the KATP-channel directly, by mechanisms independent of channel dephosphorylation.